Lokalny, regionalny czy globalny charakter rachunkowości zarządczej w ochronie środowiska - Szczypa, Piotr (Local, regional or global character of management accountancy in environment protection, 2008)
Management accountancy delivers multi-sectional information concering activity in environment protection. Depending on a range of these data it can point out local, regional and also global character of management accountancy in environment protection. In this way a amanagement accountancy becomes a system which unites information from a range of environment protection in relation to geographical areas.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 419-426